Guaranteed minimum income systems: a challenge for the twenty-first century Spanish Welfare State - Barragué,Borja (2014)
In the wake of the 2007 financial crisis, fundamental questions about economic inequality and one of its main consequences, i.e. poverty, have again garnered attention after a period in which they were largely ignored. The paper aims to be a contribution to the debate on the socio-economic effects of the 2007 crisis. It does it by drawing attention to the Spanish social safety net. First, we evaluate the impact the economic crisis has had on the Spanish households, in terms of poverty, unemployment, and inequality. We then examined the safety net in Spain, with special focus on the guaranteed minimum income system, from a comparative perspective within the legal framework of the European Union (hereinafter EU) Active Inclusion Strategy adopted in 2007. Finally, the authors propose the implementation of a guaranteed minimum income system in the national level, focusing on the relevant costs and the necessary fiscal measures to bear them.